(untitled) (Bulletin KNOB, 1999)
Huis te Linschoten is situated in the Hoge Polder in the municipality of Montfoort (province of Utrecht). In 1629 the Utrecht resident Johan Strick (1583-1648) bought a farm there. In 1638 he had the private house replaced by a ’maison de campagne’. As dean of the chapter of Old Munster Strick had a seat in the Provincial Council of Utrecht and possibly he had their architect Frederick Matthijsz. van Lobbrecht make the design. The panes bearing the coat of arms were made by Jan Gerritsz. van Bronckhorst (circa 1603-1661). Soon the stable of the farm was also replaced by a building with ground floor, two storeys and an attic. Two towers were built against the facade of the house from 1638 and finally a moat was dug around the house. Bricks were supplied by the brick maker Jan Aertsz. from Rozendaal between Haastrecht and Oudewater. The fireplace in the hall indicates the Utrecht architects Gijsbert Theunisz. van Vianen (circa 1612-1707) and Pieter Jansz. van Cooten (circa 1612-1663) to whom the castle of Renswoude and Huis de Wiers have also been attributed. The building had just been completed before the wedding of the only son Johan Strick to the aristocratic Christina Taets van Amerongen on November 30, 1647. Although the back part of the house was given a hipped roof, the new building could hardly be called a success because of the different tiles and also because it made the impression of standing back-to-front due to the high back part of the house and the low front part. In 1672 the house was plundered by the troops of Louis XIV. In 1721 an attempt was made to create greater unity of the building by bringing the front part of the house on the same level as the back part. In the second quarter of the 19th century the interior was partly rebuilt by Jan David Zocher jr. As the house had only seldom been occupied through the centuries, interiors from the 17th century (the hall) and the 18th century (the dining room) and the 19th century (the blue room) have been preserved.